A traffic-jam theory of growth - Daria Finocchiaro; Philippe Weil (Sveriges Riksbank, 2024)
We investigate the growth-finance nexus in an endogenous growth model with search frictions and congestion effects in credit and innovation markets. The interplay between these two frictions generates a nonlinear relationship between finance and growth. Financial development eases the financing of innovation but can exacerbate bottlenecks in R&D. In a calibration close to the U.S. economy, finance has a negative impact on growth. This effect is quantitatively small- consistent with the observation that, in the last century, most developed economies have experienced an expansion of the financial sector and almost constant growth rates of GDP.
Keywords: E51; G24; O40; 330; Growth; Finance; Search frictions; Technology; Innovation